Impacts of NF1 Gene Mutations and Genetic Modifiers in Neurofibromatosis Type 1 - Wang, Wei; Wei, Cheng-Jiang; Cui, Xi-Wei; Li, Yue-Hua; Gu, Yi-Hui; Gu, Bin; Li, Qing-Feng; Wang, Zhi-Chao (Frontiers in Neurology, 2021)
Neurofibromatosis type 1 (NF1) is a tumor predisposition genetic disorder that directly affects more than 1 in 3000 individuals worldwide. It results from mutations of the NF1 gene and shows almost complete penetrance. NF1 patients show high phenotypic variabilities, including cafe-au-lait macules, freckling or other neoplastic or nonneoplastic features. Understanding the underlying mechanisms of the diversities of clinical symptoms might contribute to the development of personalized healthcare for NF1 patients. Currently, studies have shown that the different types of mutations in the NF1 gene might correlate with this phenomenon. In addition, genetic modifiers are responsible for the different clinical features. In this review, we summarize different genetic mutations of the NF1 gene and related genetic modifiers. More importantly, we focus on the genotype-phenotype correlation. This review suggests a novel aspect to explain the underlying mechanisms of phenotypic heterogeneity of NF1 and provides suggestions for possible novel therapeutic targets to prevent or delay the onset and development of different manifestations of NF1.